Martindale : the complete drug reference. - Royal Pharmaceutical Society of Great Britain (London : Pharmaceutical Press, 2011)
Each entry includes Martindale identity number, titles and synonyms, CAS registry number, pharmacopoeias in which substances appear, atomic and molecular weights, chemical and physical strengths (solubility, storage, and temperature), adverse effects, and dosage.
V. A. Monographs on drugs and ancillary substances -- v. B. Preparations ; Directory of manufacturers ; Pharmaceutical terms in various languages.
Includes bibliographical references and indexes.
Published by the Pharmaceutical Press, publications division of the Royal Pharmaceutical Society of Great Britain.
Keywords: Pharmacopoeias; Pharmacopoeias -- Great Britain; Pharmacopoeias; Pharmaceutical Preparations; Drug Industry; Great Britain; Catalogs, Drug; Directories; Pharmacopoeias; Reference Materials; Books; Databases; Fulltext; Internet Resources